Internalisasi Nilai Keshalehan Sosial Melalui Pembelajaraan PAI dan Implikasinya Terhadap Pembentukan Akhlak Mulia Peserta Didik - Abdillah, Syaik; Jaki, Acep (STAI Al-Musaddadiyah Garut, 2025)
The phenomenon of declining morals of students in SMPN has become a serious problem. Deviant behavior such as lack of social awareness, low discipline, and weakening of mutual respect shows the importance of learning that does not only focus on cognitive aspects, but also affective and psychomotor. The purpose of this study is to find out: (1). The description of the internalization of social piety values ​​through Islamic Religious Education learning at SMPN 3 Bayongbong, (2) The description of the process of forming noble morals of students at SMPN 3 Bayongbong (3). The description of the implications of internalization of social piety values ​​through Islamic Religious Education learning process on the formation of noble morals of students at SMPN 3 Bayongbong. This study uses a qualitative approach with a descriptive analysis method. Data collection techniques are carried out through observation, interviews and documentation. The data sources used are primary sources of observation, interviews, and documentation and secondary sources of other references from various sources that can support this research. Data analysis was conducted through data reduction, data presentation, and drawing conclusions by maintaining the validity of the data through triangulation. The results of the study indicate that the internalization of social piety values ​​at SMPN 3 Bayongbong through Islamic Religious Education learning that emphasizes teacher role models, habituation of religious activities, and religious extracurricular activities. The implication is that students show positive changes in aspects of noble morals, which are reflected in increased attitudes of discipline, responsibility, social concern and politeness. Keywords: : internalization, social piety, islamic religious education learning, noble morals, students